Palliative care: communication as a tool in the treatment of elderly oncology patients (Research, Society and Development, 2021)
Objective: This study aimed to analyze the importance of communication strategies in humanized care in palliative care for cancer patients, so the guiding question was established: What communication strategies in the relationship between nursing professionals, cancer patients and their families in care palliatives? Methodology: This is a systematic literature review research, carried out between January and May 2020, in the Virtual Health Library, filtering the following databases: Scientific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, Database in Nursing and Medical Literature Analysis and Retrieval System Online, through the Descriptors in Health Sciences: Palliative Care; Nursing; Old man; Cancer and Communication. As inclusion criteria, studies published between the years 2015 to 2020 were defined, with full texts. The exclusion ones were duplicated studies and studies with the child population. Results: A total of 13 scientific articles published in the last 5 years and 1 book were obtained. These were analyzed and displayed in a table with 3 topics: title, author/year of publication and conclusion. Conclusion: It was observed that communication strategies must be developed based on humanized care and that professional training is an essential factor for successful nursing care.